Inferior vena cava Doppler indices in fetuses with hemoglobin Bart's hydrops fetalis - Suchaya Luewan (2018)
Objective: The purpose of this study was to assess the inferior vena cava (IVC) Doppler changes in fetuses with hydrops fetalis because of anemia, using fetuses with hemoglobin (Hb) Bart's disease as a live model. Methods: Fetuses with hydrops fetalis caused by Hb Bart's disease were measured for IVC Doppler indices. The diagnosis of Hb Bart's disease was based on fetal Hb typing. The IVC Doppler indices were compared between the fetuses in early and late hydrops fetalis. Results: Sixty-nine fetuses had satisfactory measurements, 54 in the early group (gestational age < 28weeks) and 15 in the late group (gestational age ≥28weeks). Compared with normal reference ranges, the preload index, peak velocity index, and the pulsatility index were significantly lower in the early group (p < 0.001), whereas they were significantly higher in the late group (p < 0.001). Conclusions: On the basis of evidence of IVC Doppler indices, new insight provided by this study is that in fetal anemia, cardiac decompensation is a consequence of hydrops fetalis, rather than a cause; whereas hypervolemia is the primary cause of hydrops. Additionally, cardiomegaly in most fetuses with high output hydrops fetalis is not a sign of cardiac failure but an effective adaptation to provide oxygen tissue perfusion without increased preload. © 2014 John Wiley & Sons, Ltd.